The Potential Development of Rammang – Rammang Karst Landscape As An Ecotourism In Maros Regency - Hatibu, Hardiyanti; Hanafie Prasad, Abdul Hallaf; Baharuddin, Ichsan Invanni; Nurfadilah, Nurfadilah; Azhim, Muhamad Ihsan (Universitas Negeri Makassar, 2018)
This research aims: 1) To know the aspects that support the development of land areas Rammang-rammang Karst Landscape as a tourist area. 2) To find the object that has the potential to be developed in Rammang-rammang karst landscapes. 3) To know the steps taken in the development of ecotourism in the Rammang-rammang karst landscape. Objects in this study are tourists and the public. The data presented in the form of primary data taken from questionnaires